ANALISIS LAND RENT USAHATANI PADI MENJADI USAHA BUDIDAYA IKAN PATIN DI KECAMATAN SEPUTIH RAMAN KABUPATEN LAMPUNG TENGAH - Ni Made Intan Qori Widhiani; Dwi Haryono; Ktut Murniati (Politeknik Negeri Lampung, 2022)
This research aimed to analyse the economic value of farmland (farmland rent) and determined the factors that affect convertion of paddy land into Patin fish farm at Seputih Raman Subdistrict, Central Lampung Regency. In this research the researcher employed survey method. The research location was chosen purposively with the consideration that in Seputih Raman Subdistrict there were farmers whose paddy farmlands were converted into ‘Patin fish farm and that it was also the second largest Patin fish producing area in Central Lampung Regency. Based on Roscoe’s theory, the samples of the research consisted of 30 paddy farmers and 30 Patin fish farmers. The primary (respondent interview) and secondary data (BPS data) of the research were taken from March to May 2020. The methods used in data analysis were; land rental analysis and logit analysis. The result showed that the value of the land rental on Patin fish farming per hectare per year was higher than the land rent value of the paddy farming per hectare per year. The internal factors that affected the decision to convert paddy land into the ‘Patin’ fish pondwere; age of the farmers, education background, farming experience, and land size. Besides, there were external factors that encouraged farmers to make decisions to convert paddy farmland into ‘Patin’ fish pond; they were the price of ‘Patin’ fish which was higher than paddy and the frequency of harvesting ‘patin’ fish which was little higher than paddy. The main factor that encourageed farmers to keep farming paddy was the cost of the paddy farming which was lower than ‘patin’ fish farming.